Preprints and Open Scholarship - Nancy Nyambura; Havemann, Jo (My University, 2025)
This presentation explores how preprints and open scholarship practices can strengthen the visibility, accessibility, and impact of African research. It highlights the role of AfricArxiv as a community-led platform advancing open knowledge sharing across the continent.
Accelerating African Knowledge Dissemination
Keywords: Open Scholarship; Preprints; AfricArxiv; Open Science; Inclusive Research; Open Access Week